ANALYSIS OF TEACHER WEAKNESSES IN PREPARING LEARNING OBJECTIVES IN THE LEARNING IMPLEMENTATION PLAN FOR ELEMENTARY MADRASAH LEVEL - Siti Salwa Yusyifa; Salamah (International Journal of Multidisciplinary Reseach, 2025)
Formulation of learning objectives is a crucial component in the Learning Implementation Plan (RPP), which determines the direction, process, and results of teaching and learning activities. This study aims to analyze the weaknesses of Madrasah Ibtidaiyah (MI) teachers in formulating learning objectives, especially in accordance with the ABCD model (Audience, Behavior, Condition, Degree). The research method used is a descriptive qualitative approach with documentation techniques on a number of RPPs and informal interviews for data triangulation. The results of the study indicate that most teachers have not been able to formulate complete and measurable learning objectives. The Condition and Degree components are often ignored, so that the objectives become non-specific and difficult to evaluate. In addition, the dominance of memorization-based learning, limitations in methods and media, and inconsistencies between objectives, activities, and assessments strengthen the indication of weak instructional planning. The main factors causing this weakness are low understanding of the principles of formulating learning objectives, minimal professional training, and limited institutional support. These findings recommend the need for intensive training and ongoing mentoring for teachers to improve their competence in formulating effective learning objectives, in line with the principles of constructive alignment, and relevant to the 2013 Curriculum and the Independent Curriculum.